Original paperTwenty years’ experience with percutaneous mitral commissurotomy - Chmielak, Zbigniew; Karcz, Maciej; Kruk, Mariusz; Demkow, Marcin; Kłopotowski, Mariusz; Konka, Marek; Chojnowska, Lidia; Lubiszewska, Barbara; Hoffman, Piotr; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2008)
Aim: We report our twenty years’ experience with percutaneous mitral commissurotomy (PKM). The purpose of this study was to assess temporal trends in PKM in terms of changes in patient characteristics and their impact on immediate results. Methods and results: From September 1988 to December 2007, 1564 consecutive patients underwent PKM in our department. The analysis was made to compare patients characteristics and immediate results each year. There was significant trend towards an increase in mean age (R=0.361±0.034, p <0.001), and in the echo score (R=0.157, p <0.001) of patients referred to PKM but there was no change in the number of patients who underwent PKM because of restenosis after previous surgical commissurotomy (p=0.6), and no change in pre-procedural mitral valve area (p=0.058). PKM was successful in 1563 patients. There was a significant trend toward a decrease in post-procedural mitral valve area from 2.1 cm 2 in 1988 to 1.8 cm 2 in 2007 (R=–0.228, p 2+) were similar over the years, with a mean rate of 83.1%. The rate of mitral regurgitation >2+ post PKM differed over time and decreased with a significant linear trend (R=–0.064, p=0.012). Conclusions: During 20 years patients referred to PKM become significantly older and had a less favorable anatomy, but the immediate results are still good.